Examining the effects of behavior, landscape fragmentation, and climate change on avian distributions. - Keyel, Alexander. (2017)
Abstract: I examined the patterns and processes that determine Bobolink (Dolichonyx oryzivorus) distribution and abundance. First, I tested the hypothesis that visual openness could explain area sensitivity, the pattern of species being disproportionately absent from smaller habitat patches. I compared Bobolink density and occupancy to a novel openness index, patch area, and edge effects. Our results supported a seasonally consistent openness threshold in occupancy (i.e. patches are either suitable or not). Once occupied, however, I found no relationships between patch openness or area and population density or measures of body condition (body mass, body size, circulating corticosterone levels). Despite individuals differing in response to simulated predators (flight initiation distance), differences were not related to patch area or openness. The openness response also was detected within fields, as both Bobolinks and Savannah Sparrows (Passerculus sandwichensis) placed nests both away from edges and in more open habitat when compared to expectations based on random placement. (Openness and edge were only moderately correlated.) However, I found no strong relationships between either openness or edges and reproductive success (numbers of eggs and fledglings, % of eggs producing fledglings, and nest survival), although there may be an openness effect on timing of reproduction (clutch completion date). Second, at the landscape scale, I found that climate and land use variables explained Bobolink distribution and abundance, but did a poor job of explaining the observed range shift in abundance from 1970-2008. I propose that some apparently area-sensitive species are actually responding to how open a habitat patch is, rather than to patch size. Our findings have implications for studies of area sensitivity, especially with regards to inconsistencies reported within species: specifically, (1) whether or not a study finds a species to be area sensitive may depend on whether small, open sites were sampled, and (2) area regressions were sensitive to observed densities at the largest sites, suggesting that variation in these fields could lead to inconsistent area sensitivity responses. Finally, our landscape results suggest that bioclimate models might do a poor job in predicting species range shifts due to climate change.; Thesis (Ph.D.)--Tufts University, 2012.; Submitted to the Dept. of Biology.; Advisor: J. Michael Reed.; Committee: Colin Orians, L. Michael Romero, and Christopher Elphick.; Keywords: Ecology, Conservation biology, and Wildlife conservation.